Карликові культивари роду Picea Dietr. у колекції хвойних рослин дендропарку “Олександрія” НАН України - Rubis, V.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Results of introduction of dwarf cultivars of genus Picea Dietr. in botanical establishments of Ukraine are given. The greatest collection by quantity dwarf cultivars are collected in Dendrological Park Alexandria – 18 cultivars, which belong to 4 species. The morphological characteristic of dwarf cultivars of genus Picea, which was introduction in Dendrological Park Alexandria, is given.